Exploring electrospinning for triboelectric applications - Carvalho Martins, António Maria de Botton (2023)
In the latest period, the energy crisis is an iterant topic. The world's energy demand and consumption have been on the rise with still a 78.9% of fossil fuels use. However, the transition from fossil fuels to renewable energy sources requires intense resource use. The triboelectric nanogenerators (TENGs) provide an alternative, sustainable and renewable energy source by converting mechanical energy into electrical power, due to the triboelectric effect. Their flexible, small and lightweight nature allows for applications like self-powered sensors and wearable electronics. This study presents a detailed analysis of electrospun TENGs, as well as the selection of materials, the electrospinning parameters and the triboelectric mechanisms used with 3D printed tools, to study the membrane’s greater surface area for triboelectric applications. Furthermore, SEM and FTIR analysis of the electrospun membranes is also displayed. Electrospun membranes with randomly orientated fibers were characterized for their mechanical, electrochemical and surface properties. Results showed that the best pair of membranes for electrical applications paired PVDF–TRFE and PVP polymers. Furthermore, films, bilayer composite electrospun membranes and bilayer composite films’ electrochemical properties were observed. Cellulose derivatives, CA and HPC, were also studied due to their sustainable characteristics. CA was paired with all the studied polymers being in the center between the highest and lowest potential materials. Besides PVP, interesting results were obtained when PMMA and PS were paired with PVDF-TRFE, providing the required data to analyze the electrical performance of both electrospun and films, as well as the bilayer composites. In conclusion, experimental results exhibited that electrospun TENGs provide superior electrical performance compared to film TENGs due to the larger surface area provided by the electrospun fibers.